THEORETICAL BASES OF APPLICATION OF ART THERAPY AT LESSONS OF MUSICAL ART - Шмалько, Т.А.; Білецька, М.В. (SWorldJournal, 2022)
Art therapy has become the actual method of the creative development and self-identification of the students. This method allows solving the diverse correctional, diagnostic and psychoprophylactic tasks. Therefore, the use of art therapy at the lessons of